Effects of Obstructive Sleep Apnea Syndrome and Medical Comorbidities on Language Abilities - Makanikas, Konstantinos; Andreou, Georgia; Simos, Panagiotis; Chartomatsidou, Efstathia (Frontiers in Neurology, 2021)
Objective The primary objective of the present cross-sectional study is to evaluate the semantic language abilities of patients with Obstructive Sleep Apnea Syndrome (OSAS) compared to normative data. Secondary objectives are to examine the effects of OSAS comorbidities on language test performance. Method 118 adult patients suffering from OSAS were assessed using standardized tests (Boston Naming Test, the Peabody Picture Vocabulary Test and the Verbal Fluency Test). Results Compared to normative standards, the OSAS group (age and education adjusted mean) scored significantly lower all tests (p<0.01). The OSAS group also included a significantly higher percentage of persons scoring below the 5th percentile of the normative distribution on the four tests (p<0.01). The Apnea/Hypopnea Index, O2 Desaturation index, SaO2 <85% (min) and SaO2 <75% (min) were significantly associated with language test scores (p<0.05). Moreover, higher Apnea–Hypopnea Index score and night-time oxygen desaturation were associated with reduced phonemic and semantic fluency performance only among patients with a history of hypertension and hypercholesterolemia (p<0.05). The moderating effect of diabetes and cardiovascular disease on the association between OSAS severity indices and test scores did not reach significance (p>0.6). Conclusions Results suggest that the severity of semantic language impairments in patients with OSAS is associated with the severity of the disease and intensified by common medical comorbidities (hypertension and hypercholesterolemia).